DOES JOB ROTATION AND JOB SATISFACTION AFFECT THE PERFORMANCE? - Muazza Muazza; Bonar Syarifuddin H (Management Department, Faculty of Economics and Business, Universitas Jambi, 2017)
The purpose of this research: (1) To know the description of job rotation, job satisfaction and employee performance at the Jambi Provincial Transportation Department. (2) To know the effect of job rotation on employee performance at the Jambi Provincial Transportation Department. (3) To know the effect of job satisfaction on employee performance at the Department of Transportation of Jambi Province. (4) To know the influence between job rotation and job satisfaction on employee performance at the Department of Transportation of Jambi Province.The method of this research is descriptive and quantitative and using regresion method. The population in the study were the employees of the Jambi Provincial Transportation Department. Technique of sampling research using of stratified sampling. The total sample in this study was 123 respondents.The result of the research shows that the average level of the respondent's answer for job rotation (X1) is 74.46% and the average level of the respondent answer for job satisfaction variable (X2) is 68.52, it shows highest average respondent There is in position variable rotation (X1). The magnitude of the effect of rotation variables on the performance of employees at the Department of Transportation Jambi Province is amounted to 2,427. The amount of influence of job satisfaction on employee performance variables at the Jambi Provincial Transportation Department is 4.452. Based on the analysis that together into two independent variables of job rotation and job satisfaction have a significant effect amounted to 2.201 (X1) dan 3.308(X2) on the performance of employees at the Transportation Agency of Jambi Province. Keywords: Job Rotation, Job Satisfaction, Employee Performance